Analisa Kinerja Jaringan Wireless Fidelity (Wi-Fi) 802.11AC Pada Perpustakaan Universitas Riau - Arum Parastika; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Riau University (UNRI) Library currently uses 802.11ac Wireless Fidelity (Wi-Fi) network. Even though users have used an 802.11ac Wi-Fi network, there are still problems that are often felt by users when accessing the internet such as slow connections, frequent disconnections, and difficulty connecting devices to the Wi-Fi network. Based on these problems, it is necessary to measure the performance of the Wi-Fi network at the UNRI library. Measurements were made during dense traffic using Wireshark and nperf software. The measurement parameters are throughput, packet loss, delay, and jitter. The measurement results show that the throughput and packet loss values of the 802.11AC Wi-Fi network at the UNRI library are still in the good category, with an average value of 1.935 Mbit/s, and packet loss <3 ms. However, the measured delay and jitter values are quite large, with an average delay value of 355 ms and jitter of 848.56 ms.Keywords:Wi-Fi, Throughput, Packet Loss, Delay, Jitter, Access Point, Wireshark